Property Rights, Political Connections, and Corporate Investment - Miao, Meng (World Bank, Washington, DC, 2019)
Despite the literature on rural land property rights, studies on urban land property rights are rare. This paper studies the impact of an urban land titling program on firm investment. It finds that the program leads to increased investment rate for titling firms, and the positive effect holds only for politically connected firms. The effects are likely causal, because they are more pronounced for firms that are more likely to benefit from strengthened property rights. Connected titling firms experienced fewer disputes than nonconnected titling firms after the program, and the results remain robust when using instrumental variable estimation.